Globalising Network Public Spheres. The Dissolution of the Public Sphere into Private Attention Markets - Ludes, Peter (Javnost-The Public, 2009)
The trend of the 1970s and 1980s of the previous century, which led to the so-called TV-society with para-social interactions, now has led to an all-invasive mediatisation and the dissolution of the public sphere into private attention-markets. Within this framework, only a few questions can be raised: (1) What do these trajectories imply for journalists who want to inform about distinct, controversial topics? (2) How far do new information and communication technologies advance the preparation and framing of public discourses – or do they implement a fundamentally new coding of amusement and commercialisation of attention markets? (3) How can the negligence of our conceptions of our pasts and of our futures be overcome in the up-to-the-moment news show business? These questions shall be pursued before their cross-linked answers (4) lead to a sketchy elaboration of Jürgen Habermas’ traditional concept of “a public sphere in appearance only” and an equally sketchy combination of Habermas’ and Castells’theories for a more reality-adequate concept of globalising network public spheres.